2015
DOI: 10.3889/oamjms.2015.080
|View full text |Cite
|
Sign up to set email alerts
|

Fulminate Hepatic Failure in a 5 Year Old Female after Inappropriate Acetaminophen Treatment

Abstract: BACKGROUND:Acetaminophen is a drug widely used in children because of its safety and efficacy. Although the risk of its toxicity is lower in children such reactions occur in pediatric patients from intentional overdoses and less frequently attributable to unintended inappropriate dosing. The aim of reporting this case is to attract the attention to the risk of the acetaminophen toxicity when administered in high doses.CASE PRESENTATION:We report here a 5 year old girl who developed fulminate liver failure with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…25,26 Moreover, Kasmi et al reported a 5-year-old girl who developed agitation, lethargy, jaundice, and abdominal pain due to acetaminophen toxicity caused by unintentional exposure, contributing to the development of fulminant hepatic failure. 27 Coma is one of the rare manifestations of acetaminophen overdose, the mechanism of which is not fully understood. 28 As we expected, our study demonstrated a great association between coma and the development of major outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Moreover, Kasmi et al reported a 5-year-old girl who developed agitation, lethargy, jaundice, and abdominal pain due to acetaminophen toxicity caused by unintentional exposure, contributing to the development of fulminant hepatic failure. 27 Coma is one of the rare manifestations of acetaminophen overdose, the mechanism of which is not fully understood. 28 As we expected, our study demonstrated a great association between coma and the development of major outcomes.…”
Section: Discussionmentioning
confidence: 99%